2014
DOI: 10.1111/pce.12411
|View full text |Cite
|
Sign up to set email alerts
|

High light decreases xylem contribution to fruit growth in tomato

Abstract: Recently, contradicting evidence has been reported on the contribution of xylem and phloem influx into tomato fruits, urging the need for a better understanding of the mechanisms involved in fruit growth. So far, little research has been performed on quantifying the effect of light intensity on the different contributors to the fruit water balance. However, as light intensity affects both transpiration and photosynthesis, it might be expected to induce important changes in the fruit water balance. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 52 publications
2
34
0
1
Order By: Relevance
“…Hanssens et al . () showed that the relative xylem contribution increased significantly when the light intensity was lowered by shading. Unfortunately, many of the techniques that have been used to estimate phloem and xylem influx into fruits have significant drawbacks or are based on questionable assumptions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hanssens et al . () showed that the relative xylem contribution increased significantly when the light intensity was lowered by shading. Unfortunately, many of the techniques that have been used to estimate phloem and xylem influx into fruits have significant drawbacks or are based on questionable assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of these contributions has been the objective of many studies (e.g. Ho et al, 1987;Lang & Thorpe, 1989;Morandi et al, 2007;Windt et al, 2009;Hanssens et al, 2015), but often produced contrasting results. In tomato, for example, xylem contributions ranging from 10% (Liu et al, 2007) to 75% (Windt et al, 2009) have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the same method in all sizes of trees and their organs may increase an accuracy and reliability of comparable tree water relation studies. Recently the exosensors were effectively applied in such small plant organs as tomato peduncle (Hanssens et al 2013) and truss (Hanssens et al 2015).…”
Section: Sensor Design and Configurationmentioning
confidence: 99%
“…For example, high light intensities have been demonstrated to improve dry matter content through an increase in available photoassimilates (Bertin et al, 2000;Dorais et al, 2001;Anza et al, 2006, Hanssens et al, 2015. Vapour pressure deficit (VPD) is another factor known to affect fruit dry matter content, since high VPDs increase fruit transpiration and decrease xylem influx, while phloem influx is hardly influenced (Guichard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%